Knowledge, Attitudes, and Practices of Chronic Type 2 Diabetes Patients in China Toward Continuous Glucose Monitoring: An Online Questionnaire Survey - Liu B; Wu X; Zou X; Sun F; Yu J (Diabetes, Metabolic Syndrome and Obesity)
Bingling Liu,1 Xueyi Wu,2 Xiao Zou,1 Fei Sun,1 Jie Yu1 1Department of Endocrinology, Jiujiang City Key Laboratory of Cell Therapy, Jiujiang, 332000, People’s Republic of China; 2Department of Endocrinology, The Second People’s Hospital of Guiyang, Guiyang, 550081, People’s Republic of ChinaCorrespondence: Jie Yu, Department of Endocrinology, Jiujiang City Key Laboratory of Cell Therapy, No. 1 People’s Hospital, Jiujiang, 332000, People’s Republic of China, Tel +86-18370277823, Email 47938498@qq.comPurpose: Investigate the knowledge, attitude, and practices (KAP) of type 2 diabetes patients regarding continuous glucose monitoring (CGM).Methods: A cross-sectional study was undertaken at the First People’s Hospital of Jiujiang City from Sep 20, 2023, to Dec 10, 2023.Results: A total of 633 patients with type 2 diabetes mellitus accessed the questionnaire link. Of these, 544 patients completed the questionnaires. After data cleaning, 493 questionnaires were included in the analysis, resulting in a response rate of 86% and an effective rate of 91%. Among the 493 participants, 66.9% were male, and 70.8% reported using continuous glucose monitoring (CGM). Median scores: knowledge 17 (14, 26), attitude 34 (32, 40), and practice 20 (17, 24). Positive correlations existed between knowledge and attitude (r = 0.562, P < 0.001), knowledge and practice (r = 0.653, P < 0.001), and attitude and practice (r = 0.661, P < 0.001). Logistic regression revealed that being male, participating in diabetes education, and possessing higher knowledge and attitude scores were independently associated with positive practices. Structural equation model (SEM) showed knowledge directly influenced attitude (β = 0.538, P = 0.010) and practice (β = 0.433, P = 0.010), while attitude directly influenced practice (β = 0.450, P = 0.010). Knowledge indirectly impacted practice through its influence on attitude (β = 0.242, P = 0.010).Conclusion: Type 2 diabetes patients exhibited insufficient knowledge but positive attitudes and practices toward CGM. Recommends educational interventions to enhance knowledge, potentially improving CGM utilization and outcomes in this population. Regular and comprehensive diabetes education should be integrated into routine clinical practice to optimize self-management and overall patient outcomes.Keywords: type 2 diabetes, continuous glucose monitoring, knowledge, attitude, practice